PEMANFAATAN CERITA RAKYAT PAPUA DALAM PEMBELAJARAN SASTRA YANG BERKARAKTER DAN MENCERDASKAN - Normawati NFN (Balai Bahasa Provinsi Papua, 2019)
This research focuses to analize and to give the values of Papua folklore “Cenderawasih: Unhappy birds” (Cenderawasih Burung yang Tidak Berbahagia) as the learning matter that have character and making smart. The result of this research is to show that Papua folklore can category in the concrete operational of kids story and the learning matter on text books. Literary appreciate, especially Papua folklore were understook for choosing the kids literature according to theirself. Its steps consist of their intelectually, morality,emosionally and personality, and language. Added it, literary appreciate as the part of literature attend to intrinsic aspect such as plot, characterized, theme, and moral messages.